Polar organic compounds in PM10 and PM2.5 atmospheric aerosols from a background Eastern Mediterranean site during the winter period: Secondary formation, distribution and source apportionment. (15th September 2020) - Kanellopoulos, Panagiotis Georgios; Chrysochou, Eirini; Koukoulakis, Konstantinos; Vasileiadou, Emily; Kizas, Christos; Savvides, Chrysanthos; Bakeas, Evangelos
Abstract: Atmospheric particle samples with aerodynamic diameter <10 μm (PM10 ) and <2.5 μm (PM2.5 ) were analyzed for elemental (EC), organic (OC) carbon and polar organic compounds. Samples were collected, on a daily basis, over 44 days during the winter period in Agia Maria Xyliatou, a background location of Cyprus. Polar organic compounds were determined using a 3-step derivatization method prior to analysis with GC/MS. Gas phase compounds and meteorological data were also measured. Secondary OC was estimated and found to be significantly higher in PM2.5 than PM10 fraction (mean of 0.81 ± 0.58 over 0.51 ± 0.66 μg m −3 ). Concentrations of biogenic secondary formation tracers, monocarboxylic acids, dicarboxylic acids and aromatic acids ranged from 7.3 to 29.0, 2.9–162, 7.6–82.0 and 1.9–19.6 ng m −3 respectively, in all aerosol samples, accumulated mostly on PM2.5 fraction. Molecular diagnostic ratios of selected carboxylic acids indicated influence of biogenic sources and aged aerosols. Source apportionment tools employed, including principal component analysis, demonstrated anthropogenic activity, biomass burning, biogenic volatile organic compounds oxidation and oxidation of unsaturated fatty acids as the basic sources of the studied analytes. Estimation of OC contribution from different sources was performed using tracer-based methods, such as "SOA tracer method" presenting biomass burning as a significant contributor (12.8 ± 14.8% in PM2.5 and 5.8 ± 4.8% in PM10 ). Oxidation of biogenic volatile organic compounds accounted for 13.0 ± 8.9% and 5.6 ± 3.5% of OC in PM2.5 and PM10 samples respectively. Dust episodes that occurred during the sampling period, appear to enhance secondary formation mostly on PM10 particles. Highlights: BVOCs oxidation tracers and other related polar organic species at a background area of Eastern Mediterranean. Pinene SOA showed higher contribution to OC than Isoprene SOA in PM10 samples but similar contribution in PM2.5 samples. Phthalic acid is considered as a secondary product while its isomers found to be primarily emitted. Malic acid originated from a variety of sources. Dust episodes may affect secondary formation in PM10 samples.